Features of the prosecutor's office of personnel policy Soviet Ukraine in the 1920s - Vyacheslav Slivenko (Cхід, 2016)
This article analyzes the unstudied aspects of the formation of the personnel policy of the Soviet Ukraine's prosecutor's office in the 1920s. The theme is caused by necessity of reforming the modern law enforcement. Research tasks were solved by using scientific methods, analysis, synthesis, synthesis and comparison. The author has made an analysis of personnel policy of the Soviet government in the 1920s. The purpose of this policy was a constant increase in the number of prosecutors from among the workers and peasants. This led to a significant reduction in the level of professionalism of staff. To enhance the professionalism of prosecutors government organized short-term courses and University School of Law. But they were not able to fully meet the demand for specialists. In order to improve the efficiency of the prosecutor's office in the regions of the Soviet Ukrainian government workers have established forms of staff development as a legal society. In conflict with the government prosecutors are not always won local lawlessness. Attraction prosecutors to work in government agencies has allowed to avoid conflicts. By the end of the 1920s staffing problems were solved and the prosecutor's office, began to deal with the tasks of the party elite, who actually had a monopoly on power. The dominant influence of government on the implementation of personnel policy accompanied by a prosecutor during the Soviet period. In future research the author will be related to the analysis of problems of law enforcement agencies of the state in terms of crisis and democratic reforms.